Nanowires: Quantitative Probing of Cu2+ Ions Naturally Present in Single Living Cells (Adv. Mater. 21/2016). Issue 21 (1st June 2016) - Lee, Junho; Lee, Hwa‐Rim; Pyo, Jaeyeon; Jung, Youngseob; Seo, Ji‐Young; Ryu, Hye Guk; Kim, Kyong‐Tai; Je, Jung Ho
Abstract : Quantitative probing of the Cu 2+ ions naturally present in single living cells is accomplished by a probe made from a quantum‐dot‐embedded‐nanowire waveguide. After inserting the active nanowire‐based waveguide probe into single living cells, J. H. Je and co‐workers directly observe photoluminescence (PL) quenching of the embedded quantum dots by the Cu 2+ ions diffused into the probe as described on page 4071. This results in quantitative measurement of intracellular Cu 2+ ions.